Pengaruh Sistem Pengendalian Intern Pemerintah (SPIP) dan Aksesibilitas Laporan Keuangan terhadap Akuntabilitas Pengelolaan Keuangan Desa - Setiawaty, Agus Agus (Jurnal Akuntansi dan Governance, 2025)
Objectives: To determine and analyze the effect of the Government Internal Control System (SPIP) and the Accessibility of Financial Reports on the Accountability of Village Financial Management in the Village Government in Muara Badak District.Design/method/approach: The type and source of data in this research is quantitative using primary data. The sampling technique used was purposive sampling, with a total sample of 91 respondents consisting of village government officials and BPD in 13 villages in Muara Badak District. This research uses data analysis techniques conducted with Structural Equation Modeling - Partial Least Square (SEM-PLS) using the SMART-PLS Ver 4.0 program.Results/findings: The government internal control system (SPIP) has a significant positive effect on the accountability of village financial management and the accessibility of financial reports has no significant positive effect on the accountability of village financial management.Theoretical contribution: The results of this study can be useful for further researchers and can be used as reference material, as well as add and develop knowledge, especially in the field of public sector accounting.Practical contribution: As additional insight for village financial managers to consider and pay attention to the importance of the government internal control system and the accessibility of financial reports to increase the value of village financial management accountability.Limitations: Small population and sample of only 13 villages. Limited discussion of accessibility to the accessibility of financial reports (accountability) only.Keywords: Government Internal Control System (SPIP), Accessibility of Financial Reports, Accountability of Village Financial Management.